2022
DOI: 10.3389/fphar.2022.801928
|View full text |Cite
|
Sign up to set email alerts
|

AI Models to Assist Vancomycin Dosage Titration

Abstract: Background: Effective treatment using antibiotic vancomycin requires close monitoring of serum drug levels due to its narrow therapeutic index. In the current practice, physicians use various dosing algorithms for dosage titration, but these algorithms reported low success in achieving therapeutic targets. We explored using artificial intelligent to assist vancomycin dosage titration.Methods: We used a novel method to generate the label for each record and only included records with appropriate label data to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…After removing duplicated articles, 3,346 studies were screened by the title and/or abstract, 3,175 irrelevant studies were excluded and 171 articles were included for full‐text review. Finally, 64 articles related to precision dosing using ML were included for analysis 11–74 . The PRISMA flow diagram representing the study selection process and review results is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicated articles, 3,346 studies were screened by the title and/or abstract, 3,175 irrelevant studies were excluded and 171 articles were included for full‐text review. Finally, 64 articles related to precision dosing using ML were included for analysis 11–74 . The PRISMA flow diagram representing the study selection process and review results is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…We compare our approach in Table 2 here with several works that are worked on maching learning: 89.40 Yalçın N 2022 [20] 90. 20 Wang Z [21] 91.20 Van Laere S [22] 94.79 Yalçın N 2023 [23] 91.90 Corny J [24] 81.00 Kessler, S [25] 83.65 Dos Santos HD [26] 87.1 We compare our approach here with several works that are worked on maching learning: 3 details the comparison of our best results with those obtained by other authors in the web servises composition using Artificial Intelligence. Figure 6 compares the proposed Drug-AI model with other benchmark models in terms of accuracy, and it can be seen that the accuracy of Drug-AI is higher than that of the other models.…”
Section: Evaluation and Discussionmentioning
confidence: 99%
“…23,24 A decision-tree-based model was used to personalize vancomycin dosing regimens using data from electronic health records, and similar techniques have been suggested for other drugs with a narrow therapeutic index. 74 In a large multicentre study, a reinforcement learning tool was developed to suggest the dose of erythropoietin for patients receiving haemodialysis, aiming to improve the haemoglobin level while minimizing the total doses of erythropoietin given. 75 A systematic review identified eight studies reporting machine learning models to support personalized dosing of intravenous unfractionated heparin.…”
Section: Precision Dosingmentioning
confidence: 99%
“…AI methods can support pharmacokinetic and pharmacodynamic analyses to guide drug dosing 23,24 . A decision‐tree‐based model was used to personalize vancomycin dosing regimens using data from electronic health records, and similar techniques have been suggested for other drugs with a narrow therapeutic index 74 . In a large multicentre study, a reinforcement learning tool was developed to suggest the dose of erythropoietin for patients receiving haemodialysis, aiming to improve the haemoglobin level while minimizing the total doses of erythropoietin given 75 …”
Section: How Can Ai Be Used In Clinical Pharmacology?mentioning
confidence: 99%